EVALUATION OF LOSSES OF CHILDREN'S HEALTH IN THE NATIONAL ECONOMY (INNOVATIVE ECONOMY, 2020)
Fedoryshyna L.M. EVALUATION OF LOSSES OF CHILDREN'S HEALTH IN THE NATIONAL ECONOMYPurpose. The aim of the article is the estimation of losses in the national economy from population health losses due to morbidity, disability and mortality of children.Methodology of research. The scientific works of domestic and foreign scientists on the problem under study, and the information base – data of the State Statistics Service of Ukraine are the theoretical basis of the research. General scientific methods and techniques are used in the process of work: formal logic, statistical analysis – to calculate the losses in the national economy from the loss of health in childhood; tabular – for visual representation of the obtained results; abstract and logical – when substantiating the theoretical positions and formulating conclusions.Findings. It has been established that the loss of health in childhood has direct negative consequences for the economic activity of the population of working age; in particular, depending on the degree of health loss in the child, it will more likely be seen either in the growth of the number of sick leave and temporary disability payments, or in the growth of disability pension disburs.It is substantiated that the total economic losses from childhood health losses during the period before reaching the able-bodied age will be 403.4 billion UAH or 15.8 billion dollars; from the loss of health in childhood during the period falling into the working age - 3032.6 billion UAH or 118.7 billion dollars; from childhood health losses during the period that falls on the age of older than able-bodied, - 520.1 billion UAH or 20.4 billion dollars.Originality. The further development of the research on the relationship between health and economic growth has been further developed, in particular, it has been proven that childhood health losses lead to losses in the national economy, and the size of these losses is calculated on the basis of official statistical information by 2016.Practical value. The obtained results of the study can be used in assessing the economic losses from the loss of health in childhood at the state level. In addition, the proposed methodology can be used to estimate losses at the regional level.Key words: health; morbidity; mortality; disability; economic losses; damage.
Keywords: Key words; health; morbidity; mortality; disability; economic losses; damage.